An Intelligent Fire Detection and Surveillance System - Akshaya, S; Yamini, E; Veeshal Sheev, VB; Jerin Mahibha, C (International Journal of Computer Sciences and Engineering, 2025)
Fire detectors are designed to detect one or more of the three characteristics of fire-smoke, heat and flame. The fire detection and alarm system function together to provide timely fire warnings to those in emergency zones. But the drawback is that it may include false alarms. The proposed idea is to monitor industries and to detect fire and smoke using sensors and camera. In order to save energy, space and cost, Raspberry pi 3 is used which acts as both processor and controller. The sensors detect flame and smoke using the spectrum range. If it detects any issues, then it signals the motor to sprinkle water either automatically or manually. The camera acts by detecting the thermal motion of any organisms and if any fluctuation is detected, that moment is captured and sent as a mail to the user via a third party authentication system. The videos captured by the camera are stored in cloud and is used as proof during fire accidents to claim insurance. This system also avoids false alarm.